World of Microbiology and Immunology - Lerner, K. Lee (The Gale Group, Inc, 2011)
This title in the popular World of...Series is a comprehensive, subject-specific, two-volume encyclopedic guide that covers the concepts, theories, discoveries and pioneers in microbiology and immunology for students, researchers, teachers and librarians. Using a mix of traditional academic and topical articles, World of Microbiology and Immunology addresses current ethical, legal and social issues with special emphasis given to biological warfare and terrorism. Included are 650 alphabetically arranged and cross-referenced topical and biographical entries ranging in length from 200 to 1,000 words, as well as approximately 200 photographs and illustrations.